Renovation of the Rail Head Running Surface by Plasma Welding (Current Problems in Rail Vehicles, 2025)
The contribution presents the results of cladded contact layers analyses on rails produced using plasma welding technology. The aim is to enhance the contact fatigue resistance of dynamically loaded rail sections or local repairs within the framework of predictive maintenance. The study investigates the applicability of highly alloyed austenitic steel, employing a defined cladding layer geometry to evaluate the mechanical response of the weld metal and heat-affected zones. The plasma welding technology without preheating was experimentally validated using a real profile of standard high-carbon rail steel. The results of the experimental analyses confirm the suppression of undesirable structural changes at the fusion boundary and within the heat-affected zone. The article describes the experimental procedure for evaluating the cladding, including its adhesion to the base material, resistance to wear, and susceptibility to contact fatigue damage.
Keywords: rail head; renovation; plasma welding